The complex role of MEG3: An emerging long non-coding RNA in breast cancer - Hussain, Md Sadique; Majami, Abdullah A.; Ali, Haider; Gupta, Gaurav; Almalki, Waleed Hassan; Alzarea, Sami I.; Kazmi, Imran; Syed, Rahamat Unissa; Khalifa, Nasrin E.; Bin Break, Mohammed Khaled; Khan, Ruqaiyah; Altwaijry, Najla; et al. (Pathology, research and practice, 2023)
MEG3, a significant long non-coding RNA (lncRNA), substantially functions in diverse biological processes, particularly breast cancer (BC) development. Within the imprinting DLK-MEG3 region on human chromosomal region 14q32.3, MEG3 spans 35 kb and encompasses ten exons. It exerts regulatory effects through intricate interactions with miRNAs, proteins, and epigenetic modifications. MEG3's multifaceted function in BC is evident in gene expression modulation, osteogenic tissue differentiation, and involvement in bone-related conditions. Its role as a tumor suppressor is highlighted by its influence on miR-182 and miRNA-29 expression in BC. Additionally, MEG3 is implicated in acute myocardial infarction and endothelial cell function, emphasising cell-specific regulatory mechanisms. MEG3's impact on gene activity encompasses transcriptional and post-translational adjustments, including DNA methylation, histone modifications, and interactions with transcription factors. MEG3 dysregulation is linked to unfavourable outcomes and drug resistance. Notably, higher MEG3 expression is associated with enhanced survival in BC patients. Overcoming challenges such as unravelling context-specific interactions, understanding epigenetic control, and translating findings into clinical applications is imperative. Prospective endeavours involve elucidating underlying mechanisms, exploring epigenetic alterations, and advancing MEG3-based diagnostic and therapeutic approaches. A comprehensive investigation into broader signaling networks and rigorous clinical trials are pivotal. Rigorous validation through functional and molecular analyses will shed light on MEG3's intricate contribution to BC progression.